The impact of knowledge management on organizational agility: A case study of the Riyadh Municipality (International Journal of Financial, Administrative and Economic Sciences, 2025)
This study aimed to identify the impact of knowledge management on organizational agility at the Riyadh Municipality. A descriptive-analytical approach was used, with the researcher developing a questionnaire consisting of 47 items. A comprehensive survey was conducted, distributing 103 questionnaires and receiving 84 responses. 76 questionnaires were valid for analysis, representing 73.8% of the study population. Data related to the study variables were collected and analyzed using the Statistical Package for the Social Sciences (SPSS). The results showed that both knowledge management and organizational agility at the Riyadh Municipality were at a moderate level. Furthermore, the results demonstrated a statistically significant impact of knowledge management, with its dimensions of knowledge generation, knowledge storage, knowledge sharing, and knowledge application, on organizational agility at the Riyadh Municipality. The study recommended conducting training programs and workshops to familiarize Riyadh Municipality employees with various knowledge management processes and their importance in streamlining work procedures and increasing productivity.
Keywords: Organizational Agility; Riyadh Municipality; Knowledge Management; Descriptive Analytical Approach